Gambaran Pengendalian Diabetes Melitus Berdasarkan Parameter Indeks Massa Tubuh dan Tekanan Darah di Poli Rawat Jalan Penyakit Dalam RSUD Arifin Achmad Pekanbaru - Tami Endriani Pardede; Dani Rosdiana; Erwin Christianto (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTDiabetes mellitus is a group of metabolic diseases, the characteristic is hyperglycemia that causes by abnormality of insulin secretion, insulin action, or both. The prevalence of diabetes mellitus in Indonesia was increase from previous years. Optimal controlling of DM can reduce the occurrence of metabolic disorder and chronic vascular disease. The aim of this study was to know the description of controlling diabetes mellitus based on parameters of body mass index (BMI) and blood pressure in the outpatients department of internal medicine at RSUD Arifin Achmad Pekanbaru. This research design was a cross sectional descriptive study with 51 respondents. In this study it was found that the level of controlling DM based on the parameter of BMI and blood pressure was 31,4% respondents and 39,2% respondents repeatedly can achieve the target. Meanwhile respondents who reached the target in both parameters showed 19,6% respondents, 11,8% respondents achieve the target on BMI but failed to achieve the target on blood pressure, 41,2% respondents achieve the target blood pressure but failed to achieve the target on BMI, 27,4% respondents failed to achieve the target on both parameters. It can be concluded that level of controlling DM based on parameters of BMI and blood pressure in the outpatients department of internal medicine at RSUD Arifin Achmad Pekanbaru was not reached the target.Key words : Diabetes mellitus,